2020
DOI: 10.3389/fneur.2020.00695
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Evoked Myogenic Potential (VEMP) Testing for Diagnosis of Superior Semicircular Canal Dehiscence

Abstract: Superior semicircular canal dehiscence is a bony defect of the superior semicircular canal, which can lead to a variety of auditory and vestibular symptoms. The diagnosis of superior semicircular canal dehiscence (SCD) can be challenging, time consuming, and costly. The clinical presentation of SCD patients resembles that of other otologic disease, necessitating objective diagnostics. Although temporal bone CT imaging provides excellent sensitivity for SCD detection, it lacks specificity. Because the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…We fully agree with the statement by Noij et al (1) that for the detection of semicircular canal dehiscence (SCD) "High frequency VEMP testing is superior to all other methods described to date. It is highly specific for the detection of SCD and may be used to guide decision-making regarding the need for subsequent CT imaging" (1). The ideal is a very fast, innocuous test rather than extended and uncomfortable tests such as determining the threshold for VEMPs.…”
Section: The Origin Of Vemp Tests Using High Frequencies To Identify Scdsupporting
confidence: 90%
“…We fully agree with the statement by Noij et al (1) that for the detection of semicircular canal dehiscence (SCD) "High frequency VEMP testing is superior to all other methods described to date. It is highly specific for the detection of SCD and may be used to guide decision-making regarding the need for subsequent CT imaging" (1). The ideal is a very fast, innocuous test rather than extended and uncomfortable tests such as determining the threshold for VEMPs.…”
Section: The Origin Of Vemp Tests Using High Frequencies To Identify Scdsupporting
confidence: 90%
“…In oVEMP testing, the utricle is stimulated leading to activation of the contralateral eye muscles. The use of VEMP testing has increased to assess patients with a suspected third window, and many, but not all patients with SCDS, have lowered VEMP thresholds and increased VEMP amplitudes in response to an air-conduction stimulus (depending on selected cutoff values and study populations, cVEMP and oVEMP have a sensitivity and specificity above 70%) ( 59 , 60 ). A number of studies have demonstrated that the diagnostic utility of cVEMP thresholds and oVEMP amplitudes is better than the diagnostic utility of cVEMP amplitudes and oVEMP thresholds, when using a 500 Hz tone burst or a click stimuli ( 59 , 61 63 ).…”
Section: Diagnostic Advancements and Dilemmas In Scdsmentioning
confidence: 99%
“…Another initiative to improve the diagnostic accuracy of cVEMP was the use 2,000 Hz stimulus instead of the commonly used 500 Hz tone burst. By using a 2,000 Hz tone burst, the authors of the TWI were able to increase the sensitivity and specificity (sensitivity of 92% and specificity of 100% using TWI at 2 kHz vs. 88 and 100% using TWI at 500 Hz), and they furthermore showed that cVEMP amplitude (as a normalized peak-to-peak amplitude) generated superior results ( 60 , 66 ). High frequency stimuli in oVEMP testing has also shown to be effective in differentiating patients with SCDS from normal controls (one study found sensitivity of 83% and specificity of 93% using 4,000 Hz oVEMP responses vs. 62 and 73% using 500 Hz responses) ( 67 , 68 ).…”
Section: Diagnostic Advancements and Dilemmas In Scdsmentioning
confidence: 99%
See 2 more Smart Citations